MANAJEMEN PENDIDIKAN PESANTREN AL-ULUM WAL-ALTHOF DALAM MENGUATKAN SIKAP MODERASI BERAGAMA SANTRI - Soleh, Badrus; Hasanah, Iswatul (re-JIEM (Research Journal of Islamic Education Management), 2021)
This research was conducted because it aims to find out about the function of education management in Al-Ulum Wal Althof Islamic boarding school in strengthening religious moderation. This type of research is case study research (field research) using a qualitative approach. The results of this study are educational planning at the Al-Ulum Wal Althof Islamic boarding school in strengthening religious moderation, namely by establishing formal education and cottage programs organized by schools, pesantren administrators, and Kiai where the implementation is following the schedule or written regulations which are the result of deliberation. together. The educational organization of the Al-Ulum Wal Althof Islamic boarding school is led by a Kiai who has the right of authority to distribute tasks to the school and boarding school administrators who then the school and the boarding school administrator cooperate with the parties involved such as teachers. The implementation of education at the Al-Ulum Wal Althof Islamic Boarding School is regulated in writing and scheduled so that all activities both in formal education or in pesantren run well and smoothly. Supervision of education at the Al-Ulum Wal Althof Islamic boarding school is carried out by the school and the boarding school.